Clinical efficacy of manipulation under brachial plexus block anesthesia for primary adhesive capsulitis of shoulder: a retrospective cohort study - Zhou, Haiyan; Cheng, Liming (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the clinical efficacy of manipulation under brachial plexus block anesthesia (MUA) compared to standardized conservative treatment in patients with primary adhesive capsulitis of the shoulder (ACS).MethodsThis retrospective cohort study analyzed 72 patients with primary ACS, allocated to either the MUA group (n = 36) or the control group receiving conservative treatment (n = 36). The MUA group underwent a single manipulation procedure under ultrasound-guided interscalene brachial plexus block, followed by a structured 3-month rehabilitation protocol. The control group received a comprehensive conservative regimen. Primary outcomes included shoulder range of motion (ROM) and Constant-Murley scores, assessed preoperatively and at 1, 3, 6, and 12 months post-intervention.ResultsThe MUA group demonstrated significantly greater improvement in all ROM parameters compared to the control group at all follow-up intervals (P < 0.001). At 12 months, forward flexion improved to 152.4° ± 8.7° (vs. 101.2° ± 13.5° in controls), abduction to 150.6° ± 10.5° (vs. 95.8° ± 12.3°), and external rotation to 54.6° ± 5.3° (vs. 38.2° ± 5.9°). Constant scores were significantly higher in the MUA group (86.7 ± 3.9 vs. 73.5 ± 5.5, P < 0.001), exceeding the minimal clinically important difference. Visual Analog Scale (VAS) pain scores decreased more rapidly and substantially in the MUA group (from 7.2 ± 1.1 to 1.1 ± 0.4 vs. 7.0 ± 1.2 to 2.0 ± 0.6 in controls). Patient satisfaction was significantly higher in the MUA group (93.3% vs. 75.0%, P = 0.038), with a shorter median return-to-work time (6.2 vs. 11.8 weeks, P < 0.001). Transient nerve palsy occurred in 2 MUA patients (5.6%), resolving spontaneously within 4 weeks.ConclusionMUA under brachial plexus block anesthesia is significantly more effective than standardized conservative treatment in restoring shoulder function, relieving pain, and accelerating return to normal activities in patients with primary adhesive capsulitis. The procedure demonstrates a favorable safety profile and high patient satisfaction, representing a valuable therapeutic option for conservative treatment failures. This study provides Level III evidence that MUA under brachial plexus block is superior to conservative treatment for primary adhesive capsulitis.